Influence of Strategies-Based Feedback in Students' Oral Performance - Angie Sisquiarco; Santiago Sánchez Rojas; José Vicente Abad (Asociación Colombiana de Profesores de Ingles, 2018)
This article reports on an action research study that assessed the influence of cognitive and metacognitive strategies-based feedback in the oral performance of a group of 6th grade students at a public school in Medellin, Colombia. Researchers analyzed students' oral performance through assessment and self-assessment rubrics, applied inventories to students before and after giving them the strategies-based feedback, and interviewed all students and one parent. Results showed that strategies-based feedback supported by previous strategies instruction can help students both increase the use of strategies and improve their oral performance.